Knowledge management implementation in Malaysian Public Institution of Higher Education - Suhaimee, Sirajuddin; Abu Bakar, Ahmad Zaki; Alias, Rose Alinda (2005)
Strategic Information System Planning (SISP) has been of critical importance to any type of organization for a number of years. It is also significance in the implementation of Knowledge Management in Malaysian Public Institution of HigherEducation (PIHE). A study has been conducted to get the currents status of KM implementation in Malaysian PIHE and how far Strategic Information System Planning (SISP) has been used in the implementation process. The findings will shows the needs of specific methodology for formulating Knowledge, Information and Communication Technology Strategic Planning (KICTSP) Methodology as a guideline that contains a systematic description on how to implement Knowledge Management in Malaysian Public Institution of Higher Education (PIHE).